Population abundance of insect trapped on different colours of sticky trap in pumpkin (Cucurbita moschata) field - Salmah, Mohamed; Norhayati, Ngah; Siti Nur Shafiqa, Abdullah (Penerbit Universiti Sultan Zainal Abidin, 2020)
A study was conducted to attract insects using different colours of sticky trap in pumpkin (Cucurbita moschata) field. Sticky trap was chosen as it is one of a method to estimate the insect population density in field as it requires a low cost and less skilled labour. Four different colours of sticky traps (i.e. red, white, blue and yellow) were used to determine the insect population abundance at the pumpkin field. All the traps were installed at the height of 100 cm at a random of 1 ha of pumpkin plot with five replicates for each colour and the insect samples were collected weekly for three months (October-December 2019). Overall, a total of 13,052 insects were collected throughout 11 weeks of sampling. The results showed that the percentage of insect population abundance recorded the highest was on week eight (15.01%) whilst the least abundance of insects trapped was on week one (2.28%). The most attractive colour to attract insects was significantly the yellow colour (44.34%) followed by blue (20.12%) and white (19.15%) whilst the lowest insect trapped was on red colour (16.40%). A total of nine insect orders recorded were; Diptera, Hemiptera, Coleoptera, Hymenoptera, Lepidoptera, Orthoptera, Blattodea, Isoptera and others. Diptera was the most abundant of insect’s order trapped in the yellow trap with 3427 individuals and followed by Hemiptera order (1022 individuals). Whilst the Isoptera order was the least number of insects caught on a red colour trap with only one individual. In conclusion, our findings showed that the yellow sticky trap colour is the most attractive to attract insects of C. moschata compared to other colours. Therefore, this study could provide essential knowledge that may be useful for the future ecological survey of insects of C. moschata.